Pengaruh Disiplin dan Motivasi Kerja Terhadap Kinerja Pegawai di Kantor Camat Buleleng - Widyaningrum, Ni Made Anynda; Sujana, I Nyoman (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study was conducted with the aim to analyze: (1) the influence of work discipline on employee performance at the Buleleng Sub-District Office, (2) the influence of work motivation on employee performance at the Buleleng Sub-District Office, and (3) the influence of both work discipline and work motivation on employee performance at the Buleleng Sub-District Office. This research uses a quantitative causal approach. The population of this study consists of all employees at the Buleleng Sub-District Office, totaling 60 respondents. The sampling technique used is a saturated sampling method, with the sample comprising all 60 employees. Data collection was carried out using questionnaires, and the data were analyzed using multiple linear regression. The results of this study indicate that (1) work discipline has a positive and significant effect on employee performance at the Buleleng Sub-District Office, (2) work motivation has a positive and significant effect on employee performance at the Buleleng Sub-District Office, and (3) both work discipline and work motivation have a positive and significant effect on employee performance at the Buleleng Sub-District Office.